2000
DOI: 10.1016/s0893-133x(99)00121-9
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Repetitive Behaviors and Growth Hormone Response to Sumatriptan Challenge in Adult Autistic Disorder

Abstract: Autism is heterogeneous with respect to clinical symptoms and etiology. To sort out this heterogeneity in autismAutism is heterogeneous with respect to clinical symptoms and etiology. To sort out this heterogeneity in autism, one might determine whether specific neurobiological markers vary in parallel to key clinical symptoms. Autism is characterized by three unique behavioral dimensions: social impairment, communication difficulties and rigid, restricted interests, and repetitive behaviors. One recent study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…This is in line with the relative affinities of the two drugs to the 5-HT 1D receptor. These results are in line with previous challenge studies with sumatriptan [15][16][17] but contradict others [16,18], possibly because there are two types of OCD patients -responders and non-responders to sumatriptan -depending on genetic factors such as polymorphisms at the 5-HT 1D receptor locus [19].…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with the relative affinities of the two drugs to the 5-HT 1D receptor. These results are in line with previous challenge studies with sumatriptan [15][16][17] but contradict others [16,18], possibly because there are two types of OCD patients -responders and non-responders to sumatriptan -depending on genetic factors such as polymorphisms at the 5-HT 1D receptor locus [19].…”
Section: Discussionsupporting
confidence: 89%
“…Gene therapy strategies that may alter oxytocin receptor expression in specific brain regions may eventually hold promise (Young et al, 1997). Despite the limitations of this study, the findings are potentially clinically relevant in helping to evaluate the contribution of oxytocin to one specific behavioral domain (repetitive behaviors) in autism spectrum disorder patients, and complement prior studies that link this behavioral domain to specific alterations in 5HT (Hollander et al, 2000) and immune (Hollander et al, 1999) function.…”
Section: Discussionmentioning
confidence: 63%
“…We have previously reported on the repetitive behavior domain in autism, and linked the severity of these core symptoms to one aspect of serotonin function (5HT1d sensitivity) (Hollander et al, 2000) and one specific B cell immune marker (D8/17) (Hollander et al, 1999). In this study, it was hypothesized that infusion of synthetic oxytocin might modulate the severity of this repetitive behavior domain in patients with autism spectrum disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Levels of monoclonal antibody D8/17, which identifies a B cell antigen that denotes susceptibility to rheumatic fever, were found to be increased among patients with either OCD [19] or PDD (autistic disorder) [20]. Hollander et al [21] have suggested that the 5-HT1D receptor, which was reported to be hypersensitive in OCD [22], may also be implicated in the pathophysiology of repeti-Fontenelle et al…”
Section: Discussionmentioning
confidence: 99%